The mobilizing power of Facebook in the campaign for the ongoing presidential elections 2019 in Romania – candidate Viorica D?ncil? - Bercaru, Nicoleta; Bercaru, Sorin (Technium Social Sciences Journal, 2019)
In an era of communication, technology and dependence on online social networks, Social Media are communication tools that public administrations and especially political actors must learn to use efficiently. Our objective are: (1) analysis of key performance indicators (KPIs) that facilitate the communication on Facebook of the PSD candidate, Viorca D?ncila, Coparativ with the PNL candidate, Klaus Werner Iohannis, during the presidential election campaign, (2) identify and analyze messages that generate high commitment rate from the utiizers, (3) analyzing the dominant emotions generated by the online audience.